Pembelajaran Pendidikan Agama Islam dan Self-control pada Siswa Generasi Alpha - Nuha, Agustina Kamilatun; Djamaluddin, Burhan; Makhfud, Makhfud (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
In this modern era, teenagers really need emotional intelligence training, because they are very vulnerable to unsafe conditions, both at school and outside of school. Teenagers are often easily offended, easily angered, and have difficulty controlling their emotions. One very important aspect in facing these challenges is the ability of self-control. Learning Islamic Religious Education (PAI) is one way to help them understand religious values ​​that can be a guide in controlling themselves, responding to various external stimuli, and regulating emotions in stressful conditions in the long term. This study aims to examine the effectiveness of PAI learning on the formation of self-control of Gen Alpha students at SMPN 4 Kediri. This study uses quantitative methods. Data collection uses observation and questionnaires. Data analysis uses a simple linear regression test with IBM SPSS statistics version 29. The results of this study indicate that the condition of SMPN 4 Kediri City is classified as good, has a positive and significant impact on student self-control with an R value of 0.670 and an R Square of 0.449. This means that 44.9% of students' self-control abilities can be explained by an understanding of PAI.